2008
DOI: 10.1074/jbc.m800991200
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ubiquitin-independent Internalization of Interferon α Receptor Is Prevented by Tyk2-mediated Masking of a Linear Endocytic Motif

Abstract: Linear endocytic motifs of signaling receptors as well as their ubiquitination determine the rate of ligand-induced endocytosis that mediates down-regulation of these receptors and restricts the magnitude and duration of their respective signal transduction pathways. We previously hypothesized that, in the absence of its cognate ligand, type I interferon (IFN), the IFN␣ receptor chain 1 (IFNAR1) receptor chain is protected from basal endocytosis by a hypothetical masking complex that prevents the Tyr-based end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 43 publications
(58 reference statements)
2
63
0
Order By: Relevance
“…We first tested the hypothesis of a defect in kinase activation. Tyk2 was a likely candidate because it is constitutively associated with IFNAR1 on a stretch of amino acids close to the palmitoylated cysteine (40), and it has been recently shown that the accessibility of Tyk2 to IFNAR1 depends on post-translational modifications of IFNAR1 (48). We probed this interaction using BRET, which is more sensitive than classical immunoprecipitation assays.…”
Section: Discussionmentioning
confidence: 99%
“…We first tested the hypothesis of a defect in kinase activation. Tyk2 was a likely candidate because it is constitutively associated with IFNAR1 on a stretch of amino acids close to the palmitoylated cysteine (40), and it has been recently shown that the accessibility of Tyk2 to IFNAR1 depends on post-translational modifications of IFNAR1 (48). We probed this interaction using BRET, which is more sensitive than classical immunoprecipitation assays.…”
Section: Discussionmentioning
confidence: 99%
“…However, there might be subtle differences for the expression in IFNGR between mice and humans that have to be addressed in the future. Interestingly, for Tyk2-null human cells a lack of cell surface expression of the IFN-a receptor 37 due to unmasking of an endocytic motif that is missing in the mouse receptor has been reported. 38 To prove that our mouse model is a suitable model for the investigation of kinase-independent Jak2 functions, we further investigated the role of Jak2-K882E.…”
Section: /2mentioning
confidence: 99%
“…Mammalian expression plasmids encoding C-terminal 3ϫFLAG-tagged wild-type (WT) IFNAR1 and its phosphorylation-incompetent mutant (IFNAR1-S535/539A) were previously used (22,42,43). Mammalian expression plasmids encoding 8ϫHA-tagged WT ubiquitin (tHA-Ub) and mutants (tHA-Ub-K48 and tHA-Ub-K63) were provided by Mark Hannink (University of Missouri-Columbia) (44) (45)(46)(47).…”
Section: Virus and Cellsmentioning
confidence: 99%